Understanding the impact of COVID-19 on youth sport in Australia and consequences for future participation and retention - Elliott, S.; Drummond, M. J.; Prichard, I.; Eime, R.; Drummond, C.; Mason, R. (BMC Public Health, 2021)
COVID-19 continues to represent the single biggest challenge to contemporary community sport globally. Compliance with social distancing policies, strict return-to-play protocols, and COVID-19 specific training has, perhaps, forever changed the way that children and young people engage in organised sport. Within this context, and while many children and families seek to re-engage with community sport, we (researchers and sport practitioners) have an obligation to ask questions about how the pandemic has impacted youth sport, understand the short- and long-term consequences, and explore what (if any) opportunities can be seized to assist and improve future participation and retention. The aim of this paper was to present an in-depth exploration of the impact of COVID-19 on youth sport in South Australia.